The Influence of Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence on the Performance of Employees of the Istiqlal Mosque Management Agency - Dudung Hadiwijaya; Endang Suherna (Universitas Muhammadiyah Tangerang, 2026)
This study aims to analyze the influence of intellectual, emotional, and spiritual intelligence on employee performance at the Istiqlal Mosque Management Agency. Based on the t-test results, it was found that all three independent variables—Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence—have a significant effect on employee performance, with significance values of 0.000 (< 0.05) and t-calculated values exceeding the t-table value (1.978). Intellectual Intelligence contributes 32.5% to performance and shows a moderate correlation, while Emotional Intelligence has the strongest influence with a contribution of 41.8% and a strong correlation. Spiritual Intelligence also demonstrates a strong relationship with performance, contributing 37.4%.. Furthermore, the F-test results show that intellectual, emotional, and spiritual intelligence simultaneously have a significant impact on employee performance, with an F-calculated value of 66.377 > F-table value of 2.67 and a significance value of 0.000. Statistically, the combined contribution of these three variables to employee performance is 59.8%, while the remaining 40.2% is influenced by other factors beyond the scope of this study, such as work environment, leadership, organizational culture, or other personal factors